The role of norms and collective efficacy for the importance of techno-economic vehicle attributes in Germany - Jessica Berneiser; Charlotte Senkpiel; Annette Steingrube; Sebastian Gölz (Journal of Consumer Behaviour, 2021)
The shift to electric mobility lags pursued goals. In this article we analyze the consumer's perspective and examine, which technology attributes and person-related factors influence electric vehicle (EV) adoption, and whether differences in person-related factors affect vehicle attribute importance. A total of 1922 participants took part in a Germany-wide, representative study comprising a questionnaire measuring person-related factors and a discrete choice experiment determining the importance of technology-specific attributes. Results from the choice experiment for all vehicles classes reveal that purchase price was the most important vehicle attribute. Less important for the choice of a small-sized vehicle were in descending order: range, fuel costs, fuel type, refueling infrastructure, CO2-emissions and CO2-tax. Regression analyses further indicate that subjective norms, collective efficacy, technological risk attitude and perceived information were the strongest predictors for purchase intention in the questionnaire. Participants showing high values on these factors also weighted attribute importance in the choice experiment differently, but throughout favoring EVs, than participants with low values on these factors. Factors that are disadvantageous for EV, such as range and price, were de-emphasized by these respondents. In addition, preference shares for battery electric vehicles were more than twice as high as for conventional vehicles in three out of four groups with high values. Socio-psychological factors, therefore, seem to relativize the impact of mere techno-economic factors on electric vehicle adoption. Hence, we recommend that these factors receive greater attention in the discourse on policy measures.
Keywords: 320